Report of Cabinet-appointed team of officials on mechanics of implementing a programme of academic training for defence force personnel approaching the age of compulsory retirement - Trinidad and Tobago. Team of Officials on Defence Force (Ministry of National Security, 1978)
This report identifies two possible approaches to the introduction of a policy for resettlement training--interim short-term and permanent long-term. It gives guidelines and administrative procedures for the interim programme as well as proposals regarding consequential changes in existing procedures. Proposals are made for the establishment of permanent resettlement training as well as operational procedures for the proposed permanent mechanisms. It is recommended that, as a matter of official public relations policy, the widest publicity should be given to all resettlement training programmes approved by Government for Defence Force personnel
Chairman: C. A. P. St. Hill
Keywords: Resettlement training programmes